2021
DOI: 10.1111/jvh.13572
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of entecavir versus tenofovir in preventing hepatocellular carcinoma in patients with chronic hepatitis B with maintained virologic response

Abstract: Background & Aims: Several studies suggested that efficacy of tenofovir in reducing the risk of the development of hepatocellular carcinoma (HCC) might be better than that of entecavir. It remains unknown whether a change in therapy can further reduce the risk of HCC in patients receiving entecavir therapy and achieved goal of antiviral therapy, a maintained undetectable hepatitis B virus (HBV) DNA level in the serum.Methods: A total of 1336 treatment-naïve chronic HBV mono-infected adult patients, who started… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…2A). In the 21 studies 9–20,22,24–28,45–47 reporting aHR, the pooled aHR was 0.81 (95% CI: 0.72–0.91) with significant heterogeneity ( I 2 = 47%, P = 0.007) as well (Fig. 2b).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…2A). In the 21 studies 9–20,22,24–28,45–47 reporting aHR, the pooled aHR was 0.81 (95% CI: 0.72–0.91) with significant heterogeneity ( I 2 = 47%, P = 0.007) as well (Fig. 2b).…”
Section: Resultsmentioning
confidence: 92%
“…The pooled uHR from the 24 studies 9–29,45–47 was 0.76 (95% CI: 0.67–0.86) having significant heterogeneity ( I 2 = 52%, P < 0.001) (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Our study included similar proportions of patients who first started AVT with ETV (45.0%) and TDF (55.0%), and the type of AVT was not associated with HCC development in univariate analysis. There is controversy on whether TDF is more advantageous than ETV in reducing HCC risk [ 35 ]; however, recently published studies support that the cumulative HCC risk does not change depending on the type of AVT [ 36 , 37 ]. Moreover, a recent study revealed that ETV also showed a similar risk of HCC development when compared to the newly developed tenofovir alafenamide (TAF), a substitute for TDF based on its proven efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal ultrasonography with serum alpha-fetoprotein estimation were also performed every 6 months to detect hepatocellular carcinoma (HCC) for cases in which treatment modalities with a curative intent were considered appropriate [ 23 ]. Antiviral therapy using oral nucleos(t)ide analogues was administered to patients with cirrhosis during the follow-up period, if indicated [ 24 , 25 , 26 , 27 ]. For patients with HEVs, a non-selective β-blocker, such as propranolol or carvedilol, was also administered as a prophylaxis for EV bleeding (EVB) according to physicians’ discretion, if not contraindicated.…”
Section: Methodsmentioning
confidence: 99%